A Direct Interaction Between Mitochondrial Proteins and Amyloid-β Peptide and its Significance for the Progression and Treatment of Alzheimer’s Disease - Benek, O.; Aitken, L.; Hroch, L.; Kuca, K.; Gunn-Moore, F.; Musilek, K. (Current Medicinal Chemistry, 2015)
The amyloid-β peptide (Aβ) has been associated with Alzheimer’s disease (AD) for decades. The original amyloid cascade hypothesis declared that the insoluble extracellular plaques were responsible for Aβ toxicity. Later, this hypothesis has been updated and soluble intracellular Aβ forms and their effects within the cell have come into focus. Mitochondrial dysfunction plays an important role in the pathophysiology of AD. Aβ was detected inside mitochondria and several mitochondrial proteins were found to interact directly with Aβ. Such interactions can affect a protein’s function and cause damage to the mitochondria and finally to the whole cell. This review summarizes the current knowledge of mitochondrial proteins directly interacting with Aβ and discusses their significance for the development of therapeutics in the treatment of AD.
Keywords: mitochondria